Fiqh Cooperative Learning Strategy for MTs N 12 Indramayu Students - Khuzaimah; Ibnu Rusydi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This research aims to explore the use of cooperative learning strategies in fiqh lessons. Apart from that, to develop appropriate learning models, the school and community also need to provide support for the smooth and successful learning process of students. This research method uses a descriptive qualitative approach. The research results show that Cooperative Learning Strategies in Fiqh lessons on jama' and qashar material can increase students' enthusiasm and comprehension in learning and mastering the material. Apart from that, the success of a learning process is greatly influenced by a teacher in determining and implementing strategies, methods and media that are appropriate to the material and conditions of students in a classroom lesson so that students' interest, enthusiasm and concentration in following lessons can be optimized.